PENGEMBANGAN SITUS SIGAYA UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA KELAS IV SD - Aditya Kristrifena; Yohana Setiawan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to improve the critical thinking skills of fourth grade elementary school students. The subjects in this research were 21 grade IV students at SD Negeri 03 Klepu, Pringapus District. Data collection was carried out by interviews, observation, formulating learning objectives, developing products, product trials, pretest and posttest as well as evaluation and revision. This research method uses quantitative descriptive. The research results show that SIGAYA media can improve the critical thinking skills of fourth grade elementary school students. SIGAYA Media obtained a score of 100% in material expert validation and 100% in media expert validation. Both validation results are included in the "Very valid" category. The average score for critical thinking skills obtained was the lowest score of 10 and the highest score of 90 with an average of 63. After using SIGAYA media the lowest score was 20 and the highest score was 100 with an average of 68.5. So the data can be concluded that the average score of students' pretest and posttest results increased by 5.24. SIGAYA media was declared effective because the posttest results increased from the pretest. has 0.041 which is greater than 0.05, so it is said that Ha is accepted and Ho is rejected. Ha is accepted, which means that in the pretest and posttest there are significant changes to improve the critical thinking skills of grade 4 elementary school.   Keywords: Research and Development (R&D), critical thinking, site development